Design and synthesis of new potent anticancer pyrazoles with high FLT3 kinase inhibitory selectivity - El-Deeb, Ibrahim Mustafa; Lee, So Ha (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
A new series of 1H- and 2H-pyrazole derivatives (35 final compounds) has been designed and synthesized in this study. A selected group (13 compounds) was then tested over a panel of 60 cancer cell lines at a single dose concentration of 10 mu M. At this concentration, six compounds have showed moderate to strong mean inhibitions, and were further tested at five-dose testing mode to determine their IC(50) over the 60 cell lines. The IC(50) values of the tested compounds indicated high potency (as for compound 10f) as well as high efficacy (as for compound 11e). Accordingly, compound 10f was then tested at a single dose concentration of 10 mu M over a panel of 54 kinases to determine its kinase inhibitory pro. le. The compound has showed good selectivity towards FLT3 kinase, associated with a moderate potency, with an IC(50) value of 1.74 mu M. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: TYROSINE KINASE; LEUKEMIA; CANCER; KIT